PENGARUH KESIAPAN BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS VII PADA MATA PELAJARAN IPS TERPADU SEMESTER GENAP DI SMP NEGERI 1 KENDIT TAHUN PELAJARAN 2017/2018 - Tri Astindari; Achmad Fauzi (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2018)
Based on an interview with one of the seventh grade teachers in Kendit 1 Public Middle School, he said that student learning outcomes in VII grade were still low. The low learning outcomes of social studies are partly due to their lack of learning. This was seen when social studies took place. Quantitative research design. The study was determined by the location at SMP Negeri 1 Kendit. Determination of the research location is on the Kendit highway. Data collection is obsession, interview and documentation. Quantitative descriptive data analysis. There is a low effect of reaching 0.3326 which is significant between physical readiness for the learning outcomes of grade VII students in integrated social studies subjects even in 1 Public Middle School 1 Kendit Academic Year 2017/2018. There is no influence because it reaches 0.0169 which is significant between the psychic readiness of the learning outcomes of class VII students in integrated social studies subjects in even semester 1 of Public Middle School 1 Kendit Academic Year 2017/2018. There is no influence because it reaches 0.0945 which is significant between material readiness towards the learning outcomes of class VII students in integrated social studies in even semester in 1 Kendit Middle School in Academic Year 2017/2018. From the results of data analysis and testing the hypothesis X2 and X3 above, it can be stated that psychic readiness and material readiness cannot be stated to affect student learning outcomes / in other words, material readiness and psychic readiness do not have a great influence on student learning outcomes. While in testing the hypothesis X1, it can be stated that physical readiness has a large influence on student learning outcomes.